THE REPRESENTATION OF WOMEN IN MINANGKABAU SOCIAL STRUCTURE AT TENGGELAMNYA KAPAL VAN DER WIJCK FILM - Andri Maijar; Novi Budiman; Marhen Marhen (AGENDA: Jurnal Analisis Gender dan Agama, 2021)
This article aims to assess how women in the Minangkabau social structure are represented in the film Tengelamnya Kapal Vanderwijck. This study uses a qualitative descriptive method using a scientific approach to cinematography, body language, and culture to analyze the relationship between elements including setting/attributes, ceremonial costumes. This research is dissected by the theory of social structure and feminism in Minangkabau traditional culture. The analysis of this film finds that the film Tenggelammnya Kapal Vanderwijck criticizes the position of women in the form of customary rules in Minangkabau in the decision to choose a life partner, which is determined by Uncle (mamak).